Hysteroscopic myomectomy without anesthesia - Nuria-Laia Rod; Montserrat Cubo-Abert; Laura Gomila-Villalonga; Juanjo Gómez-Cabeza; Jose Luis Poza-Barrasús; Antonio Gil-Moreno (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveScarce literature about myoma removal without anesthesia has been published. The aim of this paper is to evaluate the feasibility of a new alternative for a hysteroscopic myomectomy in a conventional office setting, without need for anesthesia.MethodsStep-by-step description of the surgical technique has been provided, based on video images. An office hysteroscopy was performed in a Gynecological Endoscopy Department of a tertiary European hospital.ResultsA 49-year-old woman was referred for management of severe hypermenorrhea. Consent and approval were received from the patient and the institutional review board, respectively. The introduction of a Truclear® hysteroscopic polyp morcellator of 5.5 mm with optic of 0 degrees into the uterine cavity did not require any kind of anesthesia or cervical dilatation. The use of saline flow helped distend the cavity and identify a submucosal myoma. Under direct vision, a full myomectomy was performed via mechanical energy with continuous cutting movements, without any complication. After the procedure was completed, the excised material was aspirated through the device into a collecting pouch. A successful complete morcellation of a Type-0 submucosal leiomyoma with a polyp morcellator device was performed in an outpatient setting. Good medical results, good tolerance by the patient besides lower surgical risks due to mechanical instead of electrical energy are shown.ConclusionIn conclusion, this video demonstrates that a hysteroscopic myomectomy can be performed successfully in office with lower risk of complications from the procedure and without use of general anesthesia besides good tolerance by the patient.